Feasibility of Intelligent Electrical Installation Trainer to Support Industry 4.0 Competency for Students of SMK PGRI 3 Malang - Wahyu Tri Handoko; Mohamad Rodhi Faiz; Mustafa Darmanto; Luthfianti Wahyu Noerlillah (Bulletin of Science Education, 2025)
The electricity industry is undergoing a transformation from conventional systems to intelligent, digitally connected, and efficient electrical networks, driven by rapid technological advancements in the Industry 4.0 era. As a result, professionals in this sector must acquire skills in emerging technologies such as automation, artificial intelligence (AI), and the Internet of Things (IoT). To address this evolving need, the Electric Power Generation study program at Vocational High School (SMK) PGRI 3 Malang has adopted a Project-Based Learning (PjBL) approach. This study investigates the feasibility and effectiveness of an Intelligent Electrical Installation trainer as a learning tool in supporting student competencies aligned with Industry 4.0 requirements. Initial observations indicated that students exhibited low interest and difficulty in understanding modern electrical systems. The implementation of PjBL is expected to increase student engagement and improve their technical capabilities in designing and implementing IoT- and automation-based electrical systems. The study employs a research and development (R&D) methodology using a branch-based ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Validation results show a high level of feasibility, with media and content experts rating it at 91.5% and student feedback at 88%. This research contributes to the field of vocational education by developing and validating an innovative, technology-driven instructional model tailored to Industry 4.0 demands. It offers practical insights into enhancing teaching strategies through project-based learning, thereby better preparing vocational students for the high-tech workforce.